2011
DOI: 10.1093/eurjhf/hfr103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute and chronic impact of adaptive servo‐ventilation on left chamber geometry and function in patients with chronic heart failure

Abstract: AimsThe aim of this study was to determine differences in the acute and chronic impact of adaptive servo-ventilation (ASV) on left chamber geometry and function in patients with chronic heart failure (CHF). Methods and resultsAn acute ASV study was performed to measure echocardiographic parameters before and 30 min after the initiation of ASV therapy in 30 CHF patients (mean age: 69 years, 23 male). The chronic effects of ASV therapy were also evaluated in 26 of these 30 patients over a mean follow-up period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 32 publications
(52 reference statements)
5
60
1
Order By: Relevance
“…These effects lead to alleviation of pulmonary congestion and mitral regurgitation. 29,30) Moreover, ASV prevents CSA and unstable breathing, which might help reduce enhanced sympathetic nervous activity. 31) In our previous reports, even single night use of ASV showed improvements in cardiac function and the suppression of sympathetic nervous activity, 20) and in addition, the short-term use of ASV decreased plasma cystatin C and increased eGFR cystatin C levels, demonstrating the possibility that cardio-renal function was improved by ASV in CHF patients with SDB.…”
Section: Discussionmentioning
confidence: 99%
“…These effects lead to alleviation of pulmonary congestion and mitral regurgitation. 29,30) Moreover, ASV prevents CSA and unstable breathing, which might help reduce enhanced sympathetic nervous activity. 31) In our previous reports, even single night use of ASV showed improvements in cardiac function and the suppression of sympathetic nervous activity, 20) and in addition, the short-term use of ASV decreased plasma cystatin C and increased eGFR cystatin C levels, demonstrating the possibility that cardio-renal function was improved by ASV in CHF patients with SDB.…”
Section: Discussionmentioning
confidence: 99%
“…5,13) Major causes that worsen adherence to ASV therapy are considered to be the discomfort from the mask itself, or the discomfort due to PAP, especially during the phase of expiration. It has recently been shown that not SDB status such as AHI, obstructive sleep apnea index, and central sleep apnea index, but "impatience" followed by "economic reasons" are related to the discontinuation of ASV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ASV treatment improves cardiac function in CHF patients. [5][6][7][8][9] Although ASV therapy has beneficial effects on CHF, the intervention is frequently rejected by CHF patients because of unpleasant feelings from the mask or positive airway pressure (PAP). It remains unknown which patient characteristics influence the smooth introduction of ASV therapy.…”
mentioning
confidence: 99%
“…An increase in cardiac output when the PCWP is high in patients with HF is considered to be a favorable effect (2)(3)(4). Furthermore, it has been suggested that the positive intrathoracic pressure produced by ASV mechanically increases the output of a failing heart as follows: 1) ASV decreases excess preload by blocking venous return, 2) ASV decreases LV afterload by outwardly pressurizing the LV and 3) ASV decreases MR (5).…”
Section: Discussionmentioning
confidence: 99%